(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Cave temple at Kudimaiyamalai consists of sanctum, ardhamandapam and a mahamandapam the front mukhamandapam was scooped out during the 7th century A.D., There are forty five inscriptions found in the Rock cut cave temple out of forty five. On the left (South) side of the sanctum sanctorum entrance Grantha inscription records the name of the 7th or 8th string Veena’s name as “Parivathini” also called as Vallabi or Vibanji. By the side of the Lord Vinayagar the famous Musical inscriptions are appeared. The inscription records about the Ragas of music or musical notes, believed to be inscribed in 7th Century. The inscription is in 7 parts and starts with Sitham Namasivaya God of music. This paper throws light on the musical inscriptions of Kudimaiyanmalai in detailed manner.